Water resource assessment, gaps, and constraints of vegetable production in Robit and Dangishta watersheds, Upper Blue Nile Basin, Ethiopia - Worqlul, Abeyou W.; Dile, Y.T.; Schmitter, Petra S.; Jeong, J.; Meki, M.N.; Gerik, T.J.; Srinivasan, R.; Lefore, Nicole (Elsevier, 2019)
The vast majority of farmers in sub-Saharan Africa depend on rainfed agriculture for food production and livelihood. Various factors including but not limited to rainfall variability, land degradation, and low soil fertility constrain agricultural productivity in the region. The objectives of this study were to 1) estimate the water resources potential to sustain small-scale irrigation (SSI) in Ethiopia during the dry season so as to expand food supply by growing vegetables, and 2) understand the gaps and constraints of vegetable production. The case studies were conducted in the Robit and Dangishta watersheds of the Upper Blue Nile Basin, Ethiopia. To document farmers’ cropping practices, field-level data were collected from 36 households who had been cultivating tomato (Solanum lycopersicum L.) and onion (Allium cepa L.) during the dry season (November – April). Two components of the Integrated Decision Support System (IDSS) - the Soil and Water Assessment Tool (SWAT) and Agricultural Policy Environmental eXtender (APEX) – were respectively used to assess impacts of SSI at the watershed and field-scale levels. Results suggest that there is a substantial amount of surface runoff and shallow groundwater recharge at the watershed scale. The field-scale analysis in the Robit watershed indicated that optimal tomato yield could be obtained with 500 mm of water and 200 to 250 kg/ha of urea applied with 50 kg/ ha of diammonium phosphate (DAP). In Dangishta, optimum onion yield can be obtained with 400 mm of water and 120 to 180 kg/ha of urea applied with 50 kg/ha of DAP. The field-scale simulation indicated that the average shallow groundwater recharge (after accounting for other groundwater users such as household and livestock use) was not sufficient to meet tomato and onion water demand in the dry season (October to April). The fieldscale analysis also indicated that soil evaporation attributed a significant proportion of evapotranspiration (60% for onion and 40% for tomato). Use of mulching or other soil and water conservation interventions could optimize irrigation water for vegetable production by reducing soil evaporation and thereby increasing water availability in the crop root zone.